Determination of Water Quality Based on Diversity of Plankton in Krueng Daroy Aceh Province - Arihsyah Putra Zai; M. Ali Sarong; Mimie Saputri (Biologi Edukasi: Jurnal Ilmiah Pendidikan Biologi, 2019)
Plankton has a very important role, especially from the feed chain (the main producer) and as a bioindicator of fertility levels, on the Krueng Daroy River. This study aims to determine the air quality of Krueng Daroy based on the level of information and to find out information in Krueng Daroy, Aceh Province. This research method is a survey with a purposive sampling technique with quantitative and qualitative approaches. Data collection was conducted for 3 sampling times, with an interval of 3 days for 9 days in 3 research locations with each location consisting of 3 stations. The usability level was analyzed by calculating the Shannon-Wiener Diversity Index, and determining the quality descriptively. The results obtained a plankton diversity index in Krueng Daroy between 2,274 to 2,565 with moderate polluted air quality. The results of the plankton process in the Krueng Daroy River are moderate, with moderate polluted air quality.